Nilai-Nilai Patriotisme Mahmoed Joenos Dalam Upaya Memajukan Pendidikan Islam Di Indonesia - Malik Alindra , Bagoes; Yunus Abu Bakar, M. (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2020)
Mahmoed Joenos as a figure of Islamic education reform tried to make significant changes to Islamic education in Indonesia. Therefore, the role of patriotism values of Mahmoed Joenos was very instrumental in Islamic education and its development to date. Education was an important means of advancing people within a nation or country. Through education, a nation will became a developed country with education. In Indonesia, education had emerged in the midst of Indonesian society when the colonizers were still occupying the State of IndonesiaFurthermore, this study used qualitative methods with descriptive analytical approaches. The type of method used was library reseach. The results of this study were about the role of patriots of Mahmoed Joenos in advancing Islamic education in Indonesia, such as: being an educator from a young, the founder of the Islamic educational institution of aj-Jami'ah al-Islamiyah and (KMI) Kulliyah al-Muallimin al-Islamiyah, the author of the Islamic education curriculum, the Pioneer of PTAI and the author of islamic education books.